Are the Recurrent Hospital Applications Inform About Domestic Violence? - Balcı, Yasemin; Kadı, Gülsüm; Göçeoğlu, Ümit Ünüvar; İnanç, Leman (The Bulletin of Legal Medicine, 2019)
Objective:The intimate partner violence is observed in all segments of society with different proportions. It can cause many different health problems in the medium-long term. In this study, we evaluated the hospital admissions in the last year in cases who were admitted to the Forensic Medicine Outpatient Clinic due to violence from his/her spouse/partner; to determine the health problems of the victims of violence and their relationship with violence.Materials and Methods: The demographic data of the patients who applied to Muğla Sıtkı Koçman University Education and Research Hospital Forensic Medicine Clinic due to the his/her spouse/partner violence between 01 June 2014 and 31 May 2017 were examined. In addition, other polyclinic/clinical applications were reviewed retrospectively in the last one year before the admission to the forensic medicine outpatient clinic.Results: Among the total 3966 cases admitted to our outpatient clinic, 198 cases (5%) were exposed to physical violence by their spouses. 177 (89.4%) of the cases were female and 21 (10.6%) were male. The mean age was 35.2 ± 10.5 (range 17-76) and the highest rate was in the 30-39 age group with 37.4%. The highest number of requests for reports was from the police headquarters on behalf of the public prosecutor with 115 cases. The mean number of applications to different units was 7.5 ± 8.5 in the last year.One-year application of cases; from one polyclinic to 10 different outpatient clinics, with 1 to 10 different symptoms/complaints. The most common complaints and symptoms related with musculoskeletal, gastrointestinal...
Keywords: domestic violence; intimate partner violence; forensic medicine; alexithymia; somatization